Teachers’ Evaluation on Seventh Graders English Coursebooks: English in Mind 1 and When English Rings A Bell Revised Edition 2017 - Pristiwati Menangsih Sabat (STKIP PGRI SIDOARJO, 2022)
This study evaluated two English coursebooks. The research questions stated in this research deal with whether English in Mind 1 and When English Rings a Bell revised edition 2017 meet the standard of a good coursebook in terms of its content, content organization, topic, skills covered in it, vocabulary, grammar, teacher’s book, work book and CD-ROM. This study was conducted by analyzing the two coursebooks by using evaluation checklist of a good coursebook and the data were triangulated by distributing the coursebook evaluation chekclists to English teachers who use the Coursebooks. The result showed that English in Mind 1 meets the standard of a good coursebooks . On the other hand, When English Rings a Bell revised edition 2017 does not meet the standard of a good coursebook in terms of its content, grammar, skills and CD-ROM. It is suggested that When English Rings a Bell revised edition 2017, can provide materials that consist of target language culture. Moreover, the grammar presented can be more varied and the language skills should be covered adequately. In addition, the coursebook should be completed with teaching aids such as audio, video or CD-ROM.